Implementasi Program Beasiswa Pemuda Tangguh di SMK Negeri 12 Surabaya - Alda Dewi Weston; Indah Prabawati; Suci Megawati; Tauran T (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to describe the implementation of the Youth Resilience Scholarship Program using the policy implementation model of Van Meter and Van Horn. This research employed a qualitative method with a descriptive design. The research was conducted at SMK Negeri 12 Surabaya. Informants were selected purposively and included the Vice Principal for Student Affairs, officials from the Governance and Public Welfare Division (Bapemkesra) of the Surabaya City Government, the school program coordinator, and scholarship recipient students. Data were collected through interviews, observation, and documentation using interview guides, observation guides, and documentation as research instruments. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana. The results indicate that the implementation of the Youth Resilience Scholarship Program has generally been carried out quite well. The variables of policy standards and objectives, inter-organizational communication and enforcement activities, economic, social, and political conditions, as well as the disposition of implementers, were categorized as good. Meanwhile, the variables of resources and the characteristics of implementing agencies have not been fully optimal due to limitations in human resources, technical issues in the reporting system, and the lack of integrated access to scholarship recipient data between the government and schools. It can be concluded that the program has contributed to supporting students' educational continuity; however, improvements are still.